Bioactive furanocoumarins from the stems and leaves of Clausena hainanensis. Issue 18 (17th September 2018) - Ma, Yan-Lei; Zhang, Chao; Zhao, Wan-Hui; Shi, Shi; He, Dan-Nv; Zhang, Pan; Liu, Xiao-Hong; Han, Ting-Ting; Fu, Yan-Hui; Liu, Yan-Ping
Abstract: A new furanocoumarin, clauhainanin A (1 ), together with seven known furanocoumarins (2–8 ), were isolated from the stems and leaves of Clausena hainanensis . The structure of1 was elucidated by extensive spectroscopic methods and the known compounds were identified by comparisons with data reported in the literature. All known compounds (2–8 ) were isolated from C. hainanensis for the first time. All isolated compounds were evaluated for their cytotoxicities against five human cancer cell lines: HL-60, SMMC-7721, A-549, MCF-7 and SW480 in vitro . Compounds1–8 exhibited significant inhibitory effects with IC50 values ranging from 1.36 to 18.96 μM. Abstract :